The City from Below: What a Challenge! Exploring Human Sustainability in Rome’s Self-Managed Places - ⁠⁠⁠⁠⁠⁠⁠Ranocchiari, Simone (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
Urban self-management is an activity that can be exhausting and may not always be sustainable over the long term. This is partly because it involves not only typical activist activities but also the management and maintenance of a physical space. Drawing on a study conducted with activists from five self-managed spaces in Rome, I analysed the mechanisms that explain why some individuals continue to engage in activism for years, despite various challenges, while others choose to leave. It became clear that the decision to stay or leave results from a delicate and complex balance between centripetal forces (which hold the activists back) and centrifugal forces (which compel them to leave). To prevent the balance from tipping towards leaving, self-managed spaces must be more than just arenas of struggle and interaction; they must also be spaces of care, which can make these experiences not only valuable but also sustainably humane.